Probiotic Bacillus subtilis LF11 Protects Intestinal Epithelium Against Salmonella Infection - Zhang, Rongling; Li, Zhengguang; Gu, Xinyi; Zhao, Jiancun; Guo, Tingting; Kong, Jian (Frontiers in Cellular and Infection Microbiology, 2022)
Enteric diseases caused by Salmonella are prevalent in poultry farming. With the forbiddance of antibiotics in feedstuff industry, Bacillus subtilis (B. subtilis) preparation as antibiotic alternatives against Salmonella infection has gained increasing attention recently. However, the protection modes of B. subtilis against Salmonella infection in broilers are strain-specific. In this study, probiotic B. subtilis LF11 significantly reduced diarrhea and mortality of broilers caused by Salmonella braenderup (S. braenderup) in spite of no inhibition effect on it in vitro. Here, the intestinal epithelial cells NCM460 was incubated to explore the protection of B. subtilis LF11 on intestinal epithelium against Salmonella. The results revealed that B. subtilis LF11 showed obvious exclusion activity with the decrease of adhesion and invasion of S. braenderup to NCM460 cells, accordingly with the increase of NCM460 cells survival compared with S. braenderup challenged alone. Meanwhile, RT-PCR and western blot proved that the gene transcription and expression levels of four tight junction proteins in NCM 460 cells were upregulated, which was further confirmed by immunofluorescence observation. Besides, B. subtilis LF11 downregulated the gene transcription levels of the proinflammatory cytokines IL-6, IL-8 and TNF-α induced by S. braenderup H9812. ELISA analysis also verified that B. subtilis LF11 reduced the IL-8 production significantly. In general, B. subtilis LF11 has the ability to protect the intestinal epithelium against Salmonella infection by reducing the Salmonella adhesion and invasion, enhancing the intestinal barrier and attenuating the enterocyte inflammatory responses and has the potential as probiotics to prevent enteric diseases in broilers.